Satellite cell activation and number following acute and chronic exercise: A mini review - Martin, N. R. W.; Lewis, M. P. (Cellular and Molecular Exercise Physiology, 2012)
Skeletal muscle satellite cells are stem cells that facilitate muscle repair and regeneration following "damage". Such "damage" occurs following exercise, and leads to activation and proliferation of these cells from their quiescent state therefore increasing cell numbers. In this mini review the likely triggers for satellite cell activation following exercise are discussed, along with the some of the recent data that shows that satellite cell number is increased acutely following exercise and chronically as a result of long term training, in a manner that appears somewhat dependent upon skeletal muscle fibre type and exercise intensity but not overall exercise type.